KEBERAGAMAAN SISWA SMA PADA LIMA KOTA BESAR DI INDONESIA - Achmad Habibullah (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
This research was aimed to know how the differsity of Senior High School seen from their level of religious education mastery, the implementation of their daily religious activities, and their socio-religious relationship. This study used a quantitative approach. The methods of collecting data were quantitative and qualitative. The data analyzed with descriptive method. The respondentsÂ of this study were students of Senior High School in big cities such as Jakarta, Bandung, Surabaya, Medan, and Makassar.The result of this study was satisfied enough and it rejected the assumption that religious education for Senior High School students was failed. The data indicated that the level of student religious mastery was good enough abd the student had implementedÂ their daily religious activities well. In the case of socio-religious relationship, 68,9% students had done it intensively, and only 12,8% students who had low intensity.